Dual drug release from CO2‐infused nanofibers via hydrophobic and hydrophilic interactions. Issue 38 (24th June 2015) - Geiger, Brett C.; Nelson, Mark Tyler; Munj, Hrishikesh R.; Tomasko, David L.; Lannutti, John J.
ABSTRACT This study investigated the effects of hydrophobic–hydrophilic interactions on dual drug release from CO2‐infused nanofibers scaffolds (PCL, PCL–gelatin, and PCL "core" PCL–gelatin "shell") using BODIPY 493/503 and Rhodamine B fluorescent dyes as drug models. Favorable dye–scaffold interactions increased total dye loading and promoted steady, more linear release. Unfavorable dye–scaffold interactions reduced overall loading and led to a greater burst release of dye. However, when CO2 was used to infuse dye into an unfavorable scaffold, the changes in loading and release were less pronounced. When two dyes were infused, these behaviors were accentuated due to interactions between the dissolved forms of the dyes. Core–shell composite nanofibers displayed radically different release properties versus pure PCL–gelatin fibers when treated with dyes via CO2 infusion. Dye release from core–shell scaffolds was highly sensitive to both interactions with scaffolds and the phase of CO2 used to infuse the compounds of interest. By using different phases of CO2 to partition dyes into hydrophobic and hydrophilic sections of core–shell nanofibers, such interactions can be manipulated to develop a bimodal drug release system with potential application in drug delivery or tissue engineering. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42571.